A second site-specific restriction endonuclease from Staphylococcus aureus. - Sussenbach, J S (1978)
A site-specific restriction endonuclease has been isolated from Staphylococcus aureus PS 96. This enzyme, Sau96 I, recognizes the DNA sequence 5'--G-G-N-C-C--3' and cleaves as indicated by the arrows. The enzyme 3'--C-C-N-G-G--5' cleaves adenovirus type 5 and lambda DNA many times, SV40 DNA 10 times and 0X174 RF DNA 2 times. Evidence is presented that the enzyme is involved in biological restriction-modification.